Respuesta :
Answer:
The correct answer option is: 4.
Step-by-step explanation:
We are given the following two functions and we are to find the value of [tex] ( f - g ) ( 5 ) [/tex]:
[tex]f(x) = x^2 - 5[/tex]
[tex]g(x) = 4x - 4[/tex]
Finding [tex] ( f - g ) ( x ) [/tex]:
[tex] ( f - g ) ( x ) [/tex] [tex]= (x^2-5)-(4x-4) = x^2-4x-5+4[/tex]
[tex]( f - g ) ( x ) = x^2-4x-1[/tex]
So, [tex]( f - g ) ( 5 ) = (5)^2-4(5)-1 = 4[/tex]
Answer:
4
Step-by-step explanation:
f(x) = x^2 - 5
g(x) = 4x - 4
(f-g) (x)= x^2 - 5 - (4x - 4)
Distribute the minus sign
= x^2 - 5 - 4x + 4
= x^2 -4x-1
Let x = 5
(f-g) (5) = 5^2 -4(5) -1
=25 - 20 -1
=5-1
=4